ANALISIS POTENSI FINANCIAL DISTRESS SEBELUM DAN SELAMA PANDEMI COVID-19 PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BEI PERIODE 2018 -2021 - Lilik Farida; Marmono Singgih; Achmad Zamroni Hazim; Ahmad Ahsin Kusuma Mawardi; Chairul Saleh; Ketut Indraningrat; Agus Priyono; Nyoman Gede Krishnabudi (Study Program of Management Faculty of Economics and Business University of Jember, 2022)
Covid-19 is pandemic throughout the world which has a huge impact on aspects of life, including Indonesia. The Indonesian government makes regulations to limit community activities, namely PSBB, which has an impact on sluggish economic conditions. This study aims to identify and analyze the differences in the potential for financial distress before and during the COVID-19 pandemic in retail companies listed on the Indonesia Stock Exchange. The sampling of this research uses purposive sampling method, the data used is secondary data, namely the financial statements of retail companies for 2018-2021. In this study, we analyze financial distress using the Altman Z-Score theory which has been modified by calculating several financial ratios in a discriminant. In this study using the T test which in the normality test carried out the data were not normally distributed. Therefore, the study was tested using a non-parametric test, namely the Wilcoxon test. The results of the study show that there are differences in the financial distress of retail companies before and during the covid-19 pandemic.